2007
DOI: 10.1534/genetics.107.070672
|View full text |Cite
|
Sign up to set email alerts
|

Divergence Between the Drosophila pseudoobscura and D. persimilis Genome Sequences in Relation to Chromosomal Inversions

Abstract: As whole-genome sequence assemblies accumulate, a challenge is to determine how these can be used to address fundamental evolutionary questions, such as inferring the process of speciation. Here, we use the sequence assemblies of Drosophila pseudoobscura and D. persimilis to test hypotheses regarding divergence with gene flow. We observe low differentiation between the two genome sequences in pericentromeric and peritelomeric regions. We interpret this result as primarily a remnant of the correlation between l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
128
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 105 publications
(150 citation statements)
references
References 49 publications
22
128
0
Order By: Relevance
“…2011), and because they are a parallel case to that of D. pseudoobscura and D. persimilis , where inversions do appear to maintain the species barrier (Noor et al. 2007). Comparisons between sympatric and allopatric populations of the two Heliconius species have shown that almost a third of the genome is admixed in sympatry and that hybridization has been ongoing for a long time (Martin et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2011), and because they are a parallel case to that of D. pseudoobscura and D. persimilis , where inversions do appear to maintain the species barrier (Noor et al. 2007). Comparisons between sympatric and allopatric populations of the two Heliconius species have shown that almost a third of the genome is admixed in sympatry and that hybridization has been ongoing for a long time (Martin et al.…”
Section: Discussionmentioning
confidence: 99%
“…2007; Noor et al. 2007), where major fixed inversions occur on most chromosomes. Although H. melpomene and H. cydno have similarly divergent genomes overall compared to the Drosophila species pair, we do not find evidence for a similar role for inversions in maintaining the species barrier.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chromosomal rearrangements such as inversions (an orientation reversal of a piece of DNA within a single chromosome) impact species divergence by reducing recombination in heterokaryotypes [2,[4][5][6]. For paracentric inversions, which do not span a centromere, a single meiotic recombination event between heterokaryotypes results in acentric and dicentric products-both of which do not produce viable gametes (electronic supplementary material, figure S1).…”
Section: Introductionmentioning
confidence: 99%
“…This suppressed effective recombination between heterokaryotypes of paracentric inversions may facilitate speciation by protecting locally adapted alleles inside the inversions from gene flow with other populations, allowing further divergence between two karyotypes (reviewed in earlier studies [9,10]). While theoretical [11 -14] and empirical [15 -21] support for this hypothesis exists, the maintenance of genomic divergence-within inversions over long time periods (many hundreds of thousands of generations), and the shape of elevated divergence-within inversions have been less explored empirically (but see [2][3][4][5]). …”
Section: Introductionmentioning
confidence: 99%